Redrawing the past: the value of colours in a graphic narrative / Muhamad Azhar Abdullah and Hafizah Rosli - Abdullah, Muhamad Azhar; Rosli, Hafizah (Faculty of Art and Design, 2025)
Graphic novels that are adapted from real-life events or the lived experiences serve as a platform for visual representation of the relationships between memory and storytelling. Graphic storytelling that is based on lived experiences place significance in the evidence of subsisting elements outside the frame which allow the readers to use their imagination in bringing still images to life. When appropriately developed, visual narratives that are enhanced with colours could effectively reflect reality through the passage of time. This paper seeks to analyse the use of colours in enhancing the significance of visual narratives that could affect the psychological connection and the recollection of social history in readers by utilising content analysis. It suggests that the application of colour aspects and colour schemes not only enhance a visual narrative but stimulate psychological responses and emotional reactions while correspondingly communicates the artistic intent and meaning.